Prehistoric Myths in Modern Political Philosophy - Widerquist, Karl; McCall, Grant S. (Book collections on Project MUSE., 2019)
How modern philosophers use and perpetuate myths about prehistory The state of nature, the origin of property, the origin of government, the primordial nature of inequality and war - why do political philosophers talk so much about the Stone Age? And are they talking about a Stone Age that really happened, or is it just a convenient thought experiment to illustrate their points? Karl Widerquist and Grant S. McCall take a philosophical look at the origin of civilisation, examining political theories to show how claims about prehistory are used. Drawing on the best available evidence from archaeology and anthropology, they show that much of what we think we know about human origins comes from philosophers' imagination, not scientific investigation. Key Features Shows how modern political theories employ ambiguous factual claims about prehistory Brings archaeological and anthropological evidence to bear on those claims Tells the story of human origins in a way that reveals many commonly held misconceptions